Hubungan Program Pengobatan Kanker terhadap Konsep Diri Wanita dengan Carsinoma Mammae - Yuli Permata Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to study the relationship of treatment programs to self-concept in women with mammary carcinoma in the Polyclinic Surgery Clinic of RSUD Dr. Achmad Mochtar Bukittinggi. The design of this study uses descriptive analytic methods. The results of this study were obtained by more than half of respondents who undertook treatment programs at the poly surgical clinic of RSUD Dr. Achmad Mochtar Bukittinggi is 19 people (63.3%) and more than half obtained a low self-concept in women with carsinoma mammaes as many as 16 respondents (53, 3%) in the poly surgical clinic of Dr. Achmad Mochtar Bukittinggi Hospital. The statistical test results obtained p value = 0.046, it can be concluded that there is a relationship between the treatment program for women with mammary mobilinoma in the surgical clinic of RSUD Dr. Achmad Mochtar Bukittinggi with an OR value = 0.130. Keywords: Mammae Cancer, Self Concept, Cancer Treatment Program